Optimal pricing and service level in supply chain considering misreport behavior and fairness concern. (December 2022) - Qu, Shaojian; Shu, Lingli; Yao, Jingyuan
Abstract: In the supply chain, there exists the phenomenon that misreport behavior and fairness concern coexist. The reference point for fairness concern is usually upstream publicly disclosed profit, whereas upstream may hide its true information. Few research investigates the phenomenon deeply. To address the gap, this paper studies a supply chain consisting of a manufacturer with possible misreport behavior and one retailer with possible fairness concern. Four Stackelberg game supply chain models are constructed. Optimal decisions and profits under different scenarios are solved simultaneously and compared, and find that: Firstly, the manufacturer's misreporting behavior is harmful to the retailer. Secondly, the retailer's fairness concern behavior will shorten the manufacturer's profit and help itself to face manufacturer's misreport behavior. Thirdly, face to the retailer's fairness concern, the manufacturer can benefit from appropriately misreporting. Through numerical analysis and extension to one-to-many general situation, the above findings are verified and analyzed. Highlights: Four Stackelberg game models with behavioral factors are developed. Asymmetric misreporting behavior damages the retailer. Appropriately misreporting helps the manufacturer face retailer's fairness concerns. Fairness concern salvages retailer's losses caused by upstream misreporting.